Islam, Feminism, and Gender: Islam, feminisme dan gender - Sahrudin Udin; Zahra Maia Asyasyra (Bulletin of Islamic Research, 2024)
Feminism assumes that there is an unequal position between men and women in society, so efforts need to be made to eliminate the gender gap so that there are equal rights between men and women. For feminism, gender exists in every aspect of human life. And this research aims to reveal how Islam views feminism and gender equality in the Quran. This research uses a qualitative approach by applying the descriptive-analytical method. The result of the research is that in Islam the position of men and women is the same from the point of view of the Qur'anic verses studied.